Sustainable Livelihood Strategy for Red Onion (Allium Ascalonicum L.) Farmers in Pajeng Village, Gondang District Bojonegoro Regency - Ika Puspitasari; Sujarwo; Fitria Dina Riana (Jurnal Penelitian Pendidikan IPA, 2024)
The main commodity that is favored by the people of Pajeng Village, Bojonegoro Regency is shallots, because apart from being able to be cultivated in both the rainy and dry seasons. There are sustainability obstacles which has an impact on the sustainability of shallot farming. Therefore, an appropriate livelihood strategy is needed for adaptation to improve livelihoods for sustainable survival. Livelihood Vulnerability Index and descriptive analysis were used to answer the research objectives. Meanwhile, SEM-PLS analysis to answer the next research objective is to analyze livelihood assets, livelihood risks, livelihood strategies and welfare of red onion farmers. The level of mastery of livelihood assets is in the medium category with an index value of 2.08. The highest asset control is physical capital at 2.34 and human capital at 2.22. The level of vulnerability of the livelihood assets of shallot farmers is in the medium category with an LVI vulnerability index value of 0.49. The highest vulnerability value for financial capital is 0.71, while the livelihood asset with the lowest vulnerability for physical capital is 0.37. Livelihood risks have a significant effect on livelihood assets, livelihood strategies and welfare.